The Validity and Reliability of an Instrument to Measure Physical Science Teachers' Topic Specific Pedagogical Content Knowledge in Stoichiometry. Issue 2 (4th May 2019) - Malcolm, Stephen Andrew; Mavhunga, Elizabeth; Rollnick, Marissa
Abstract : Stoichiometry, which deals with the quantitative aspects of Chemistry, is a topic students find challenging and which teachers struggle to teach. South African students' performance in stoichiometry in the final matriculation examinations has led to calls for the topic to be taught better and highlighted the need for teacher professional development. This served as the rationale for this study to design an instrument to measure the quality of experienced Physical Science teachers' topic-specific pedagogical content knowledge (TSPCK) using a mixed-methods approach. Responses by five teachers to open questions on each of five components of TSPCK were used to generate scenario-based items for the instrument. The validity of the instrument was determined through Rasch analysis of responses of a sample of 31 teachers. Both the validity and reliability of the instrument to measure the quality of TSPCK in stoichiometry were found to be acceptable based on the fit statistics and reliability measures generated from the Rasch analysis.